2021
DOI: 10.3390/su132011224
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Opening of Producer Services on the International Competitiveness of Manufacturing Industry

Abstract: Countries participating in the international division of labor each try to occupy the industrial highlands, obtain competitive advantages, and promote sustainability of economic development. Based on Porter’s Diamond model, it is widely believed that producer services are vital to support the manufacturing industry. Consequently, this paper selects samples of 55 countries and uses data from 2010 to 2017 to empirically test the impact of producer service’s opening on the export competitiveness of the manufactur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…Factor conditions are necessary to compete in an industry (Porter, 1990, p. 71) which affects international competitive success (Yu et al, 2021). They are often grouped into five broad categories: human, physical, knowledge, and capital resources as well as infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Factor conditions are necessary to compete in an industry (Porter, 1990, p. 71) which affects international competitive success (Yu et al, 2021). They are often grouped into five broad categories: human, physical, knowledge, and capital resources as well as infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is especially important for the manufacturing industry, which plays a significant role in the sustainable economic development of the country. The manufacturing industry spreads to other sectors, thereby increasing the overall productivity of the entire economy, enabling it to compete in the global market (Yu et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A su vez, (Lee et al, 2021) expresan que una combinación de las estrategias genéricas de costos y enfoque mejora la rentabilidad empresarial. Desde el "Diamante de Porter", (Yu et al, 2021) sostienen que el análisis de las industrias de apoyo es vital para obtener ventajas competitivas sostenidas y promover el desarrollo económico.…”
Section: Ventaja Competitivaunclassified
“…In 2020, Sholihah et al [131] proposed a methodology to help manufacturing enterprises analyze their development status and select the appropriate competencies to develop service-oriented strategies, and validate the applicability of the methods through practical applications in enterprises. In 2021, Yu et al [132] analyzed a sample of dozens of countries and manufacturing companies worldwide and concluded that servitization could increase its advantages and take over critical competitive capabilities internationally. In the same year, Liang et al [133] introduced a novel deep reinforcement learning approach to solve some combinatorial optimization problems of services in cloud manufacturing and demonstrated through comparative experiments that the method has a good performance both in terms of effectiveness and generalization capability.…”
mentioning
confidence: 99%
“…Figure14. The articles about the field of manufacturing servitization[2,3,47,[123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138] .…”
mentioning
confidence: 99%